The Public Administration of Hotel Businesses in LuangPrabang City, Luangprabang Province. - SOMSAMONE, Vilayphone; SISAVANH, Orlathai; SOUNTHALY, SengAloun; SENGCHANH, Souksamone; MIXAYKONE , Khanthaly; INTHAJACK, Bualoy (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
The hotel business is a major component, which becomes a driving force of tourism sector in Luang Prabang. The hotel service businesses, a key sector, has promoted, expanded and disseminated unique local values through the development of new innovation to assistdriving hotel management practices. Public sector management studies are in line with the roles, jurisdictions and duties as specified in the Decree on Tourism Business Management, which in Luang Prabang, the Department of Information, Culture and Tourismhas an important role in managing the hotel mangagement in cooperation with LuangPrabang Heritage Office as well as related provincial departments. The overall performance of the hotel business towards the public administration was “moderate” (3.36, S.D = 1.09). Planning on a “high” level (3.42; S.D = 1.09). Controlled by “very high” levels, (3.44; S.D = 1,10). Organizations rated “moderate” (3.32; S.D = 1.12). With “Moderate”, (3.27; S.D = 1,11). In order to ensure the sustainable management of the hotel business in Luang Prabang, there are four possible aspects: planning, control, organization and leadership of the public administration in the hotel business in Luang Prabang. Specifically, for the sustainability of the hotel business, this research has found the following: 1. To survive the crisis in a timely manner; 2. To strengthen public-private partnerships related to hotel business; 3. To raise awareness, thus the hotel business operators recognize the importance of public sector management; 4. To develop public sector personnel who have sufficient business management expertises; 5. To review ASEAN Standard Checks with the Three-Star Hotel Business and 6. To provide clear POLC Framework Orientation. Proposals from this research include: The public sector should establish a data collection team to evaluate the implementation of the hotel business management periodically. In addition, the public sector needs to increase the quantity and quality of the specialists who can closely monitor the operation of each hotel. Additionally, those can encourage the close cooperation among the businesses to avoid inter-company competition, especially when it comes to hotel pricing. Finally, the standardization of the hotel primarily depends on the ministry and the provincial levels, leading to hotel management fragmented and limited.